Comparative efficacy of neuroprotective agents for improving neurological function and prognosis in acute ischemic stroke: a network meta-analysis - Wang, Yuchen; Li, Mengqi; Jiang, Yuye; Ji, Qiuhong (Frontiers in Neuroscience, 2025)
BackgroundIschemic stroke is the second leading cause of death and the third leading cause of combined disability and mortality globally. While reperfusion therapies play a critical role in the management of acute ischemic stroke (AIS), their applicability is limited, leaving many patients with significant neurological deficits and poor prognoses. Neuroprotective agents have garnered attention for their potential as adjunct therapies; however, their relative efficacy remains unclear. This study utilized a network meta-analysis (NMA) to systematically compare the efficacy of neuroprotective agents in improving neurological function and prognosis in stroke patients.MethodsThis study adhered to PRISMA guidelines and the Cochrane Handbook for systematic reviews. Randomized controlled trials (RCTs) were identified through comprehensive searches of the PubMed, Embase, and Cochrane Library databases. Two independent reviewers conducted the selection process, data extraction, and quality assessment. Outcomes included 90-day modified Rankin Scale (90d-mRS), change of National Institutes of Health Stroke Scale score from baseline to 90-day/14-day/7-day (90d/14d/7d-NIHSS) and 90-day/14-day Barthel Index (90d/14d-BI). Data analyses were performed using RevMan 5.4 and Stata 14.0.ResultsA total of 42 RCTs involving 12,210 participants were included in this analysis. The interventions assessed included Cerebrolysin, Citicoline, Edaravone, Edaravone Dextranol, Human urinary kallidinogenase, Minocycline, Nerinetide, Butylphthalide, Vinpocetine, and Control. The NMA results demonstrated that NBP ranked highest for the 90d-mRS, 90d-NIHSS, 14d-NIHSS, and 14d-BI outcomes. Edaravone was found to be the most effective intervention for the 7d-NIHSS and 90d-BI outcomes.ConclusionThe findings of this study indicate that different neuroprotective agents exhibit distinct advantages at specific stages of recovery. NBP showed outstanding performance in improving 90d-mRS and 90d-NIHSS, underscoring its potential in long-term rehabilitation. Edaravone demonstrated significant superiority in 7d-NIHSS scores, highlighting its role in early neuroprotection. These results provide valuable insights for individualized clinical treatment. To further validate the efficacy and safety of neuroprotective agents, future studies should involve larger sample sizes and conduct multicenter, large-scale randomized controlled trials.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=601346, identifier CRD42024601346.